EVALUASI PEMBELAJARAN BAHASA MENGGUNAKAN TAKSONOMI BLOOM MULAI DARI VERSI LAMA SAMPAI VERSI REVISI - Agus Wismanto (Sasindo, 2014)
Learning paradigm actually tried to include various perspectives appraisal or assessment. In this case, the school with the learning paradigm focused not on quantity, but the quality of graduates, the aggregate growth of learning, and the development of learning technology. Changes in attitude and behavior are used as indicators that a student has experienced a learning event can vary, from simple to very complex. However, changes in behavior as evidence of the learning output can be classified into dimensions or categories, each of which has formal characteristics. There are different categories of learning outputs presented people who each have differences and similarities. One category of learning output is presented Benjamin Samuel Bloom. The description of taxonomy bloom, and to facilitate the teachers / lecturers / learners in choosing the appropriate verb associated with the purpose of learning, basic competencies and indicators of achievement, assessment, and so on. Here is a list of options that can be used verbs in cognitive (knowledge). Good luck, hopefully useful!Keywords: evaluation, learning a language, BLOOM.